Vibrational spectroscopy studies on linear polyamines - Marques, M. P. M. (2007)
Vibrational spectroscopy [both Raman and INS (inelastic neutron scattering)], coupled to quantum mechanical calculations, was used in order to perform a thorough structural analysis of linear polyamines and polynuclear polyamine metal chelates [e.g. with Pt(II) and Pd(II)] with potential anticancer activity. The complementarity of the Raman and INS spectroscopies was exploited in order to gain a better knowledge of the conformational behaviour of these systems. Moreover, the conjugation of the experimental spectroscopic data to the theoretical results allows us to obtain valuable information on the structural preferences of this kind of system, which may lead to the establishment of SARs (structure-activity relationships) ruling their biological activity. Some of the most significant results obtained by the 'Molecular Physical-Chemistry' Research Group of the University of Coimbra (Portugal) are reviewed here.